The Promise of Property: Legal Optimism and Collective Efficacy in Chicago's Urban Agriculture District. (12th November 2020) - Ela, Nate
Abstract: This article explains how and why community organizers in Chicago's Englewood neighborhood have found promise in the opportunities that property law provides for addressing community problems. Drawing on interviews and ethnographic fieldwork, it examines the creation of neighborhood institutions for Chicago's first urban agriculture district. These institutions have been informed by memories of slavery and sharecropping, and of the role played by food production and economic cooperation in struggles for African American self-determination. To keep ownership, use, and benefits of urban farmland local, organizers in Englewood founded a community land trust as a way to cultivate a sense of community ownership and control, and as a way to chip away at the alienation that blocks residents from addressing local problems. Prior studies have linked collective efficacy and residents' individual sense of ownership; the experience in Englewood points to how collective efficacy could also be fostered by institutions that demonstrate collective, African-American ownership of community resources. The article discusses why organizers and residents in race-class subjugated communities may find promise in the sense of sovereignty and legal agency afforded by property.